PEMBUATAN PERANGKAT KOTAK INSTRUMEN TERPADU (KIT) PRAKTIKUM PADA MATERI INDIKATOR ASAM DAN BASA - Fatin Khairunnisa; Rini Muharini; Husna Amalya Melati (EduChem, 2021)
The aim of this study is to discover the adequacy of Practicum toolkit box on acid and bases subject that was developed based on the adequacy assessment by expert and teachers and students’ responses. The subject of this study was acid and bases Practicum KIT that was tested to 10 students of SMPN 2 Selakau in an initial field test and also to 36 students from 3 middle schools (SMP) in amain field test, and, furthermore, five science teachers in the main field test from the same three schools. Evaluation sheet of the KIT adequacy and questionnaire were used for data-collection. The result of data processing showed the KIT that was developed is acceptable to be used in learning process through the standards of material, language, graphic, and KIT media with validity coefficient score 1. Moreover, on the report of percentages calculation of questionnaire, the result of student questionnaires in the initial field test and main field test had collected the average of percentages, which were 82.62% and 87.27% with a very high criteria, and for the teacher questionnaires, the number of the average of percentages was 91.77% with a very high criteria as well.